2014
DOI: 10.2478/10004-1254-65-2014-2415
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of advanced oxidation processes in lowering bisphenol A toxicity and oestrogenic activity in aqueous samples

Abstract: Bisphenol A (BPA) is a well-known endocrine disruptor with adverse oestrogen-like effects eliciting adverse effects in humans and wildlife. For this reason it is necessary to set up an efficient removal of BPA from wastewaters, before they are discharged into surface waters. The aim of this study was to compare the efficiency of BPA removal from aqueous samples with photolytic, photocatalytic, and UV/H 2 O 2 oxidation. BPA solutions were illuminated with different bulbs (halogen; 17 W UV, 254 nm; and 150 W UV,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Conversely, others have shown that even when organisms degrade BPA with high RE, intermediates formed during degradation are often more toxic than the parent compound (Mtibaà et al 2018). Similarly, chemical technologies such as photocatalytic oxidation did not reduce BPA toxicity but even increased it in comparison with untreated BPA solution (Plahuta et al 2014).…”
Section: Toxicity Of Medium Containing Bpamentioning
confidence: 90%
“…Conversely, others have shown that even when organisms degrade BPA with high RE, intermediates formed during degradation are often more toxic than the parent compound (Mtibaà et al 2018). Similarly, chemical technologies such as photocatalytic oxidation did not reduce BPA toxicity but even increased it in comparison with untreated BPA solution (Plahuta et al 2014).…”
Section: Toxicity Of Medium Containing Bpamentioning
confidence: 90%
“…(Growth Inhibition Test). The in-vitro tests called YES (Yeast Estrogen Screen) and YAS (Yeast Androgen Screen), using Saccharomyces cerevisiae yeast strains, turn out to be useful for assessing estrogenic or androgenic activity [56].…”
Section: Toxicological Testsmentioning
confidence: 99%
“…In contrast, simple and inexpensive bioassays represent a very useful tool in the safe implementation of the treatment technologies (Konstantinou and Albanis, 2003), a scarcely studied aspect in the case of photocatalytic systems (Bozzi et al, 2004). The eventual detoxification of different matrices by the use of AOTs (Konstantinou and Albanis, 2003;Bozzi et al, 2004) and the acute toxicity of TiO 2 nanoparticles to freshwater aquatic organisms (Hall et al, 2009) have been assessed by different techniques, e.g., luminescent bacteria (Bozzi et al, 2004;Hall et al, 2009;Oturan et al, 2008;Plahuta et al, 2014), algae (Hall et al, 2009;Oturan et al, 2008;Andreozzi et al, 2004), microinvertebrates (Bozzi et al, 2004;Oturan et al, 2008;Plahuta et al, 2014;Andreozzi et al, 2004;Nagel-Hassemer et al, 2011) and fishes (Hall et al, 2009;Plahuta et al, 2014;Nagel-Hassemer et al, 2011). However, chronic toxicity studies during application of AOTs have scarce records.…”
Section: Introductionmentioning
confidence: 96%